Evaluation of Turbojet Engine with Water Injection for Aircraft Use as Controlled Object - Alexandru-Nicolae Tudosie; Mihai Lungu (Aerospace)
This study addresses an under-represented topic in turbojets’ design—the characterizing of this type of engine as an entity subject to automatic control. This study’s subject is a medium-size turbojet, improved with a water injection system for thrust augmentation, and evaluated as a controlled object. The method of coolant injection in the compressor and/or in the combustion chamber of the aviation engine has been intensively studied and applied for the temporary increase in thrust. After a period of abandonment, the method seems to be returning in a version that also produces a reduction in pollutant emissions. Starting from determining turbojet performances on the test rig and establishing the equations that define the turbojet as a system, the mathematical model for both versions (basic and with a water injection) was issued. In order to correlate the basic engine operation with the water injection, a version of control architecture was designed, containing two controllers (for engine’s speed and for the injected water flow rate). An embedded control system was described by its mathematical model; based on its equations, its block diagram with transfer functions was issued. The system’s quality was evaluated by performing studies that concern the turbojet’s main parameters (speed and combustor temperature) and time behavior (system response at step input), which led to some results and conclusions regarding how the water injection changed the properties of the engine as a controlled object: the engine has become slower with bigger static errors for the studied parameters (affecting the stabilization at their values imposed by the new operating regime). The proposed method, based on the characterization of the engine as a controlled object (with and without coolant injection), can be very useful as a method of predicting the behavior of any turbojet when the addition of coolant injection system is desired; obviously, the appropriate modeling of both the turbojet and the injection system is necessary.